The Capacities of Coast Guards to deal with Maritime Challenges in Southeast Asia - Prabhakaran, Paleri (2016)
Southeast Asia embarked on a determined journey towards progressive and sustainable socioeconomic well-being under the umbrella of ASEAN that will turn 32 this year. The result is visible. The vast and complex maritime dimension of Southeast Asia is a major determinant of the challenges the region face. The maritime challenges are examined with reference to law enforcement and services under national and international obligations of the governments of the region. The idea of a coast guard is important here. The coast guard is an old concept in a new appreciation in the post-UNCLOS world. It is the ideal force to establish rule of law and provide services at sea by their international acceptance and operational focus. The sea farers are at ease to communicate and interact with the coast guard. The costal communities are free to interact with them. They could also enhance confidence building measures between nations, the much needed geopolitical ingredient in troubled times. The governments have to appreciate and understand the role of the coast guard in safeguarding the maritime and other national interests in their identified maritime zones. Then only they will acquire the necessary capacity and competence. Against this background the working paper examines the maritime challenges of Southeast Asia and the capacity of its coast guards to deal with them under the presumption that the potential for military engagements in future is limited in the region.